Development and Validation of an Abbreviated Questionnaire to Easily Measure Cognitive Failure in ICU Survivors: A Multicenter Study. Issue 1 (January 2018) - Wassenaar, Annelies; de Reus, Jorn; Donders, A. Rogier T.; Schoonhoven, Lisette; Cremer, Olaf L.; de Lange, Dylan W.; van Dijk, Diederik; Slooter, Arjen J. C.; Pickkers, Peter; van den Boogaard, Mark
Abstract : Objectives: To develop and validate an abbreviated version of the Cognitive Failure Questionnaire that can be used by patients as part of self-assessment to measure functional cognitive outcome in ICU survivors. Design: A retrospective multicenter observational study. Setting: The ICUs of two Dutch university hospitals. Patients: Adult ICU survivors. Interventions: None. Measurements and Main Results: Cognitive functioning was evaluated between 12 and 24 months after ICU discharge using the full 25-item Cognitive Failure Questionnaire (CFQ-25). Incomplete CFQ-25 questionnaires were excluded from analysis. Forward selection in a linear regression model was used in hospital A to assess which of the CFQ-25 items should be included to prevent a significant loss of correlation between an abbreviated and the full CFQ-25. Subsequently, the performance of an abbreviated Cognitive Failure Questionnaire was determined in hospital B using Pearson's correlation. A Bland-Altman plot was used to examine whether the reduced-item outcome scores of an abbreviated Cognitive Failure Questionnaire were a replacement for the full CFQ-25 outcome scores. Among 1, 934 ICU survivors, 1, 737 were included, 819 in hospital A, 918 in hospital B. The Pearson's correlation between the abbreviated 14-item Cognitive Failure Questionnaire (CFQ-14) and the CFQ-25 was 0.99. The mean of the difference scores was –0.26, and 95% of the difference scores fell within +5 and –5.5 on a 100-point maximum score. Conclusions: It is feasible to use the abbreviated CFQ-14 to measure self-reported cognitive failure in ICU survivors as this questionnaire has a similar performance as the full CFQ-25. Abstract : Supplemental Digital Content is available in the text.